2018
DOI: 10.1097/md.0000000000011175
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of lung microbiota in the patients with obstructive sleep apnea

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 26 publications
(29 reference statements)
1
10
0
Order By: Relevance
“…Increased abundance of class Fusobacteriia was associated coal type used in the homes of our subjects. Although we are the first to report these associations with Fusobacteria , to the best of our knowledge, it is consistent with recent studies that have found lung‐derived Fusobacteria to be associated with sleep apnea (Lu et al, ) and asthma (Millares et al, ).…”
Section: Discussionsupporting
confidence: 91%
“…Increased abundance of class Fusobacteriia was associated coal type used in the homes of our subjects. Although we are the first to report these associations with Fusobacteria , to the best of our knowledge, it is consistent with recent studies that have found lung‐derived Fusobacteria to be associated with sleep apnea (Lu et al, ) and asthma (Millares et al, ).…”
Section: Discussionsupporting
confidence: 91%
“…In addition to the upper respiratory tract, the microbiome profile of the lower airway has been studied through bronchoscopy and bronchoalveolar lavage analyses. The levels of Proteobacteria and Fusobacteria were significantly higher, whereas the level of Firmicutes was significantly lower in patients with OSA compared with control patients [74]. A healthy airway microbiota is essential to maintain airway immunity and reduce the risk of infection.…”
Section: Othersmentioning
confidence: 88%
“…2018; Lu et al . 2018 a ). Firmicutes, Proteobacteria and Fusobacteria were significantly different in both lung and oral samples from people with OSA compared with controls (Xu et al .…”
Section: Overviewmentioning
confidence: 98%
“…2018; Lu et al . 2018 a ). Interestingly, seven genera of the nasal microbiota correlated with apnoea–hypopnoea index (a measure of disease severity) in OSA (Wu et al .…”
Section: Overviewmentioning
confidence: 98%